GREEN SYNTHESIS OF NANOPARTICLES FROM PLANT SOURCES FOR TEXTILE APPLICATION - A. PADMA, PUSHPALATHA KYATHAM and (The Journal of Research, PJTSAU, 2019)
Textiles are infected very easily by microbes which create health problems to the consumers. To avoid and control the infection and infestation from micro organisms, antimicrobial finishes are given to them. There are a number of natural and synthetic antimicrobial agents that can be applied on textiles. In the present study an attempt was made to finish cotton textiles with nanoparticles from plant sources to impart the antimicrobial finish. Finish was applied to cotton knitted textiles using pad-dry-cure method with curing at 35° to 40°C. The antibacterial activity was evaluated by a modified qualitative test method AATCC-147, 2004 against both Staphylococcus aureus and Escherichia coli. It was found that all the treated samples with all combinations indicated better antibacterial resistance. Fabric treated with Cassia and silver nanoparticles were found to possess high antibacterial resistance.